A near-infrared large Stokes shift probe based enhanced ICT strategy for F- detection in real samples and cell imaging. Issue 51 (20th December 2019) - Hu, Qinghua; Huang, Qiuxiang; Mao, Yu; Liu, Xinlin; Tan, Fangrong; Wang, Yuyuan; Yin, Qiang; Wu, Xumeng; Wang, Hongqing
Abstract: In view of the few reports of the near-infrared emissive probe for fluorine ions, we herein designed and synthesized a new easy-to-get colorimetric and near-infrared emissive fluorescent probe (IS-NR-F ) with a large Stokes shift (>127 nm). Based on specific F − triggered desilylation reaction induced enhanced ICT strategy involving the donor phenolate anion and the acceptor malononitrile, the probe exhibited dual colorimetric and fluorescent turn-on responses, and provided excellent selectivity for fluoride ions. The fluorescent response at 665 nm displayed very good linear relationship in the wide concentration range and deduced a low detection limit of 0.09 ppm. The detection mechanism was confirmed by 1 H NMR, ESI-MS, and TLC calculation. Moreover, probe IS-NR-F has been successfully employed to detect F − in tap water, toothpaste samples, and fluorescent imaging of F − in HeLa cells. Graphical abstract: Image 1 Highlights: A new dicyanoisophorone derived near-infrared fluorescent probe was synthesized with a large Stokes shift (127 nm). The probe performed an excellent selectivity for F − by naked eyes. The probe exhibited a wide detection range with a good linear relationship for F − . The probe was applied to detect F − in toothpaste samples and imaging in living cells.